Nurturing Creativity whilst Caring: Participatory Action Research with family carers and a Recovery College - Bowness, Bryher; Begum, Samina; Bicknell, Sarah; Samuels, Lana; Shah, Sudhir; Hess, Stephanie; Martin, Karen; Bark, Debbie; Henderson, Claire; Lawrence, Vanessa (Frontiers in Psychiatry, 2025)
IntroductionThe benefits of attending Recovery Colleges for mental and social wellbeing are well-documented, but the experiences of family carers (roughly 6–11% of students) are underexplored. Family carers report that attending courses supports their own wellbeing and recovery journeys, but also call for greater recognition and relevant provision from Recovery Colleges.Materials and methodsThis Participatory Action Research project was codesigned by a Family Carers Advisory Group, an academic researcher, and staff at a Recovery College in England. We aimed to expand Recovery College provision to promote family carers’ wellbeing, by coproducing and coevaluating a creative course exploring self-care. We collected data through online feedback forms, fieldnotes, photographs and participatory reflective sessions, and collaboratively explored the family carers’ experiences of the course through inductive reflexive thematic analysis.ResultsSeven family carers enrolled on our three-part online course Nurturing Creativity Whilst Caring. They shared photographs of the creative and self-care activities they took part in during the course, and gave feedback about what they found helpful and what could improve. We developed three themes summarizing their learning: ‘self-care as a family carer is complex, but there are small steps we can take to create time to nurture ourselves’, ‘creativity connects family carers with others and ourselves’, and ‘nurturing a creative mindset for caring’.DiscussionThis example shows how Participatory Action Research can be an effective approach to designing courses for family carers in a Recovery College. We explore deeper understandings of self-care whilst caring, and the ways creativity can enable this and have wider reaching benefits. Our findings also add to the literature on implementing adult education in practice in Recovery College settings. Finally, we provide some implications for improving courses for family carers and future research.